Tổng hợp bột hiđroxyapatit kích thước nano bằng phương pháp kết tủa hóa học - Hương, Đào Quốc; Ngọc Bích, Phan Thị (Vietnam Journal of Chemistry, 2014)
Hydroxyapatite (HA) powder was synthesized by simple precipitation method using H3PO4and Ca(OH)2at the different temperatures. The obtained HA samples were examined using methods of XRD, SEM, FTIR and TGA. The investigations indicated that precipitating at ambient temperature can create the single phase HA powder with the particle size under 100 nm.